POSTMODERNISM AND PSYCHOLOGY. A PENDING ISSUE - Pinillos Díaz, José Luis (Anales de Psicología / Annals of Psychology, 2002)
With Renaissance, Psychology became atomistic, it defended the law of inertia, and it adopted a deterministic view - from which it arises the possibility to make computations independent of contents or the computed symbols-, and later, at the 19th Century, it adopted mechanism as the rest of the natural sciences. For such reasons, Psychology has stayed reluctant to Postmodernism. Establishing the relationships between Psychology and Postmodernism involves to accept, on the one hand, that current natural science is different from that existing one century ago, and on the other hand, that postmodern theories are not necessarily less rational than modern ones, in the frame of which Psychology was conceived. Since, at the extreme, Postmodernism represents the illegitimization of modernity, the author is inclined to introduce a new concept, that is, the "commodification" - an abstractive process through which objects are segregated from the physical, psychical, and socio-cultural contexts in which such objects were generated, to be reduced to terms of economical benefit-. It is from that new concept, that Psychology is called for.